2010
DOI: 10.1111/j.1095-8649.2010.02788.x
|View full text |Cite
|
Sign up to set email alerts
|

Using rapid assessment and demographic methods to evaluate the effects of fishing on Heterodontus portusjacksoni off far‐eastern Victoria, Australia

Abstract: A rapid semi-quantitative ecological risk assessment method (productivity and susceptibility analysis) indicated that, despite its low biological productivity, the Port Jackson shark Heterodontus portusjacksoni is at low risk to all fishing methods in far-eastern Victoria, Australia, under the present fishing practices, because of its low catch susceptibility. The risk to this population, however, would increase if the shark gillnet fishery operating in the region were to retain the species as a by-product. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Yet, given the robust nature of the species to fishing activities (Frick et al 2009(Frick et al , 2010a(Frick et al , 2010b, the egg-laying behaviour (Rodda 2000;Powter and Gladstone 2008c) and the fact that Port Jackson shark by-catch is not retained; this species may have a low risk of fisheries-induced population declines. This assessment of the susceptibility of the Port Jackson shark is consistent throughout the species range (Jones et al 2008;Powter and Gladstone 2008a;Tovar-Á vila et al 2010). Because population structuring is not apparent, this generalised evaluation of resilience to decline could be cautiously assigned to regional populations throughout the distribution of the Port Jackson shark.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Yet, given the robust nature of the species to fishing activities (Frick et al 2009(Frick et al , 2010a(Frick et al , 2010b, the egg-laying behaviour (Rodda 2000;Powter and Gladstone 2008c) and the fact that Port Jackson shark by-catch is not retained; this species may have a low risk of fisheries-induced population declines. This assessment of the susceptibility of the Port Jackson shark is consistent throughout the species range (Jones et al 2008;Powter and Gladstone 2008a;Tovar-Á vila et al 2010). Because population structuring is not apparent, this generalised evaluation of resilience to decline could be cautiously assigned to regional populations throughout the distribution of the Port Jackson shark.…”
Section: Resultsmentioning
confidence: 98%
“…The Port Jackson shark is commonly caught as by-catch by commercial and recreational fishers throughout the species distribution range (Walker et al 2005;Jones et al 2010), and accordingly, has received interest from fishery scientists, as assessments of the population demography of the Port Jackson shark have been made for south-eastern Australian populations (Powter and Gladstone 2008a;Tovar-Á vila et al 2010). However, no assessment has been made of the population age structure of the Port Jackson shark for South Australia, the approximate centre of the species distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using only a quantitative assessment were the demographic modelling approaches of Punt & Walker (1998), Simpfendorfer et al (2000) and Aires‐da‐Silva & Gallucci (2007); the level 3 PSA of Cortés et al (2010) and the SAFE (Sustainability Assessment for Fishing Effects) technique of Zhou & Griffiths (2008). García et al (2008) and Tovar‐Ávila et al (2010) incorporated semi‐quantitative and quantitative approaches. In the case of Tovar‐Ávila et al (2010), who worked within the ERAEF framework, a level 2 risk assessment (PSA) was augmented with a level 3 risk assessment that included demographic modelling.…”
Section: Approaches Used In Erasmentioning
confidence: 99%
“…For example, Aires‐da‐Silva & Gallucci (2007) concluded that through demographic modelling, the higher biological productivity of the P. glauca decreased its overall risk of overexploitation to commercial fishing in the Atlantic Ocean, yet that the juveniles should receive protection from harvest. Similarly, Tovar‐Ávila et al (2010) cited the low discard mortality rate of the Port Jackson shark Heterodontus portusjacksoni (Meyer 1793) in Australian fisheries by‐catch as driving its low vulnerability to exploitation. Conversely, other studies have found certain species to be highly vulnerable to by‐catch due to low productivity, decreased mobility and schooling behaviour, such as S. megalops (Braccini et al , 2006), the school shark Galeorhinus galeus (L. 1758) (Punt & Walker, 1998), the whiskery shark Furgaleus macki (Whitley 1943) (Simpfendorfer et al , 2000) and various benthic non‐skate batoids (Astles et al , 2009).…”
Section: Species Assessedmentioning
confidence: 99%
See 1 more Smart Citation